Current developments in biotechnology and bioengineering : designer microbial cell factories: metabolic engineering and applications - Joshi, Swati (Elsevier, 2022)
Designer Microbial Cell Factories: Metabolic Engineering and Applications, the latest release in the Current Developments in Biotechnology and Bioengineering series, provides a detailed overview of the biotechnological approaches and strategies used to generate engineered microbes and to facilitate the acceleration, modulation and diversion of metabolic pathways to get desired output such as production of value-added compound or biodegradation of xenobiotic pollutant. The book also highlights applied aspects of designer microbes in fields as diverse as agriculture, pharmaceuticals and bioremediation. Designer microbes generated through reprogramming the microbial cell factories (MCFs) provide an edge over their natural counterparts in terms of increased molecular diversity and selective chemistry. These bugs are becoming instrumental in several areas, including agriculture, environment and human health. Engineering microbes through directed evolution not only gives freedom from evolutionary constrains but also allow introduction of regulated and foreseeable functions into MCFs.